The Evaluation Study of Nutritional Knowledge from Sports Practitioners in The Quadrennial National Sports Competition 2021 - Mohammad Arif Ali; Gustiana Mega Anggita; Said Junaidi; Sugiarto Sugiarto; Siti Baitul Mukarromah; Dewi Marfu'ah Kurniawati; Etika Ratna Noer; Zainudin Amali; Donny Wira Yudha Kusuma; Leo Nacion Santillana; Anggit Wicaksono; Adiska Rani Ditya Candra (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2022)
Background: Nutritional program is another influencing factor of athletic performance after the physical training program, and psychological training program. However, Indonesian sports practitioners somehow still neglect the important role of sports nutrition to achieve the best athletic performance.Objectives: To examine the level of basic nutritional and sports nutritional knowledge among the sport’s practitioners who participated in the quadrennial national sports competition 2021.Materials and Methods: This evaluation study has conducted with a descriptive quantitative approach. Thirty-eight sports practitioners (24 males and 14 females), were represented from five provinces such as Central Java, Western Java, Eastern Java, Southern Sumatera, and Bali. Their status during the sports events are athletes, referees, officials, coaches, and judges. The incidental technique sampling was used to attract the respondents. Nutritional Knowledge Questionnaires (NKQ) developed by Rosi et al, was used in this study. Data was analyzed with the frequencies distribution technique, and displayed using the percentage.Results: More than half of the total respondents (81%) have good, very good, and excellent knowledge in general nutrition (21%, 34%, 26%) respectively. Similarly, it is also happened in the evaluation of their knowledge for basic nutrition good (5%), very good (29%), excellent (40%), as well as in their knowledge levels for sports nutrition, good 18% and excellent 53%. However, based on the evaluation of their sports nutritional knowledge, we found that there are 8% (n=3) of the respondent were failed as the score <50 points.Conclusion: Overall, the nutritional knowledge for general, basic and sports in sports practitioners evaluated good. However, the sports nutritional knowledge is not well understood evenly by them. At last, this study can be used as a reference to make a better decision on how sports nutrition must be promoted to maximize the athletic performance.